Transmission and biosafety risk of SARS-CoV-2 by aerosols generated during dental procedures - Mendoza Murillo, Paúl (2020)
The transmission and biosafety risks of aerosols containing SARS-Cov-2 produced by rotating instruments, which are a source of viral load for dentists potentially vulnerable to infection. According to studies carried out at Princeton University, the SARS-CoV-2 coronavirus is detectable in aerosols for up to three hours, during which time dentists would be directly exposed to inhalation of viral particles in aerosols, especially when patients are in the incubation period and are asymptomatic. The WHO states that airborne transmission occurs when there is a presence of microbes within the nuclei of Flügge droplets which can remain in the air for long periods of time and be transmitted at distances greater than a meter, what is known as suspended particles or aerosols. Its nature can predispose transmission of SARS-CoV-2; hence, the importance of knowing the characteristics of the transmission risk and recommending prevention and control measures in order to block the probability of becoming infected.